Problem-Based Learning and German as a foreign language - Corbacho Sánchez, Alfonso (Magazin, 2025)
It is generally accepted that problem-based learning (PBL) has proved to be very efficient in the teaching and learning of most disciplines and this also includes the teaching of a second language. In this paper, which is based on the use of exercises and activities related to this methodology, the advantages of PBL applied to German as a foreign language are considered and highlighted. It is contended that the innumerable variety of aspects and scenarios encompassed in communication, together with the entertainment element that PBL activities always entail, make this approach especially effective and attractive, although some difficulties may also arise with the use of this methodology.